Transrectal ultrasound (TRUS) as a diagnostic tool for abscesses and fistulas of the anus. Anatomy and methodology of the TRUS examination - Łukaszewska, Ewa; Jasiuk, Ilona; Chrościński, Kamil (Journal of Education, Health and Sport, 2024)
Introduction Transrectal ultrasound (TRUS) is a valuable imaging technique used to diagnose abscesses and fistulas in the anorectal region. It provides detailed visualization of soft tissues and anatomical structures, making it a crucial tool for assessing conditions that are often challenging to diagnose with other methods. Our work explores the anatomy relevant to TRUS and outlines the methodology of the examination, emphasizing its importance in the accurate detection and treatment planning of anorectal disorders. Aim of the study To evaluate the effectiveness of transrectal ultrasound (TRUS) as a diagnostic tool for identifying and assessing abscesses and fistulas in the anorectal region. Methods and materials This review was conducted based on available data published in the PubMed database, using the following phrases: "TRUS”, „abscess", „diagnosis of fistulas”, and ”anorectal disorders”. Conclusion Transrectal ultrasound (TRUS) has proven to be a highly effective diagnostic tool for the detection and evaluation of abscesses and fistulas in the anorectal region. Its ability to provide clear visualization of soft tissues and complex anatomical structures enhances diagnostic accuracy, facilitating more precise treatment planning. By outlining the anatomical context and proper methodology for TRUS, this study highlights the technique’s value in improving clinical outcomes for patients with anorectal disorders. Further research and refinement of TRUS protocols may continue to optimize its diagnostic potential.